Analisis Fungsi Manajemen Konstruksi Dalam Pembangunan Gedung Komersil - Sonia, Gina; Desfita, Mediana; Nasmirayanti, Rita; Sari, Kharisma Permata (JURNAL RIVET, 2025)
Commercial buildings are buildings that accommodate various commercial functions such as villas, hotels, resorts, trade, rental office space, and others. According to their type, commercial buildings are buildings that are planned and designed to generate profits for both owners and users. Based on this thinking, commercial building design considers nine aspects (Wungow, 2011). Factors that must be considered in the construction of commercial buildings and actions taken so that the construction management function has a significant influence on the success of commercial building construction projects in project development. From its definition, construction management applies management functions to a project by utilizing resources effectively and efficiently to achieve project objectives. The main goal of construction management is to manage management functions effectively and efficiently to obtain optimal results as agreed with the project owner. The selected sampling techniques were Interviews/Questionnaires and Primary Data. In this study, a sample of 25 respondents from several different construction service companies was required. Based on Company Status, company type, company work experience, work equipment aspects, capital/finance, HR (Human Resources). Analysis of construction management factors in commercial building construction, analysis of questionnaire data taken from 25 respondents was processed using Microsoft Office Excel 2010.